HAK IMUNITAS PELAKSANA UNDANG-UNDANG KEBIJAKAN KEUANGAN NEGARA DI MASA PANDEMI COVID-19 - Novy Listiana (Badamai Law Journal, 2021)
This research was conducted using a research method, the type of normative legal research, the type of norm obscurity research, the problem approach using the legal approach, conceptual approach, case approach, historical approach and a comparative approach, the nature of this research is prescriptive, the types and sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials obtained through library research. From the results of this research, it is found that first, the concept of the right to immunity that exists and is given to the implementer of the law is the concept of limited immunity rights, aka not absolute with the limitation of "good faith", so this concept does not violate the principle of equality before the law. Second, what can be used as a benchmark for good faith includes the conversion of the Discretionary Provisions of Law Number 30 of 2014 concerning Government Administration..